The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/bpa.12521
|View full text |Cite
|
Sign up to set email alerts
|

Modeling tau pathology in human stem cell derived neurons

Abstract: Tau pathology is a defining characteristic of multiple neurodegenerative disorders including Alzheimer's disease (AD) and Frontotemporal Dementia (FTD) with tau pathology. There is strong evidence from genetics and experimental models to support a central role for tau dysfunction in neuronal death, suggesting tau is a promising therapeutic target for AD and FTD. However, the development of tau pathology can precede symptom onset by several years, so understanding the earliest molecular events in tauopathy is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…8a). This is in agreement with previous reports showing that the iPSCderived neurons do not contain any forms of multimeric or aggregated tau in the absence of additional triggers such as tau mutations, overexpression or seeding [55,56]. Similarly, no significant differences were observed between control, sAD and fAD lines when comparing Phosphorylation at the sites above the red line, which corresponds to p-value = 0.05, is significantly higher in Braak III-IV samples the levels of pS198, pS199, pT231 and pS416four sites that were significantly increased in brain tissues from Braak III-IV donors (Fig.…”
Section: Five Consistently Increased Tau Ptms Differentiate Braak Stasupporting
confidence: 94%
See 1 more Smart Citation
“…8a). This is in agreement with previous reports showing that the iPSCderived neurons do not contain any forms of multimeric or aggregated tau in the absence of additional triggers such as tau mutations, overexpression or seeding [55,56]. Similarly, no significant differences were observed between control, sAD and fAD lines when comparing Phosphorylation at the sites above the red line, which corresponds to p-value = 0.05, is significantly higher in Braak III-IV samples the levels of pS198, pS199, pT231 and pS416four sites that were significantly increased in brain tissues from Braak III-IV donors (Fig.…”
Section: Five Consistently Increased Tau Ptms Differentiate Braak Stasupporting
confidence: 94%
“…However, when we studied the tau PTM signature in iPSC-derived neurons from sporadic and familial AD patients, we found that the pattern we observed in human brains was not recapitulated, which might be due to their developmental immaturity and the absence of tau oligomerization in these cells. Developing cellular models for AD and especially to study tau is challenging [56]. Despite many advantages, iPSC-derived neurons have the caveat that they express only one out of six isoforms of tau [53], and reprogramming results in the loss of aging factors, which may affect disease pathology [54,72].…”
Section: Discussionmentioning
confidence: 99%
“…7a). This is in agreement with previous reports showing that the iPSC-derived neurons do not contain any forms of oligomeric or aggregated tau in the absence of additional triggers such as tau mutations, overexpression or seeding [44, 45]. Similarly, no significant differences were observed between control, sAD and fAD lines when comparing the levels of pS198, pS199, pT231 and pS416, four sites that were significantly increased in brain tissues from Braak III-IV donors (Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, when we studied the tau PTM signature in iPSC-derived neurons from sporadic and familial AD patients, we found that the pattern we observed in human brains was not recapitulated, which might be due to their developmental immaturity and the absence of tau oligomerization in these cells. Developing cellular models for AD and especially to study tau is challenging [45]. Despite many advantages, iPSC-derived neurons have the caveat that they express only one out of six isoforms of tau [42], and reprogramming results in the loss of aging factors, which may affect disease pathology [43, 61].…”
Section: Discussionmentioning
confidence: 99%
“…The directed differentiation of induced pluripotent stem cells (iPSC) into speci c neuronal subtypes provides an unlimited supply of human neurons that can be used to study disease mechanisms. Multiple groups have used this approach to successfully study tauopathies (11). While this is a promising approach, a major challenge is overcoming the developmental regulation of tau; during fetal stages, the 0N3R isoform constitutes the majority of tau (12,13), a phenomenon recapitulated in iPSC-neurons by multiple groups (14,15).…”
Section: Introductionmentioning
confidence: 99%